Predicting progression to AML. (July 2018) - Sellar, Rob; Jaiswal, Siddhartha; Ebert, Benjamin
The number, identity, and burden of mutations in clonal hematopoiesis are associated with the risk and timing of progression to acute myeloid leukemia.